A comparative study of the CISG and the North Korean contract law as to formation of a contract. Issue 1 (27th February 2020) - Kim, Sang Man
Abstract : Purpose: North Korea joined the United Nations Convention on Contracts for the International Sale of Goods (CISG) as a 90th member on March 27, 2019, which will necessitate the understanding of North Korean laws, in particular, the contract law for sale. This paper aims to compare the CISG and the North Korean contract law as to the formation of a contract focusing on form and writing requirement, offer and acceptance. Design/methodology/approach: This paper analyzes the provisions of the North Korean Civil Code and the CISG and reviews the previous research studies concerning the formation of a contract. Findings: The CISG and the North Korean Civil Code are very similar in many aspects as to the formation of a contract. However, there are some discrepancies as to the formation of a contract to which the parties need to pay attention in choosing the governing law. Practical implications: The parties need to pay attention to the differences concerning the formation of a contract between the North Korean Civil Code and the CISG in concluding a contract for sale with North Korea. Originality/value: This paper will be the first research work, to the best of the author's knowledge, on the comparison of the CISG and the North Korean contract law as to the formation of a contract.